Pelatihan Pembuatan Lembar Kerja Peserta Didik (LKPD) untuk Guru SMP di Kota Bandar Lampung - herpratiwi; Yulianti, Dwi; Nurwahidin, Muhammad; Riswandi; Firdaus, Rangga; Pradini, Susanthi; Handoko; Sugiyanto (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2023)
Teachers in learning have not used LKPD which they designed themselves correctly. Meanwhile, the demands of the curriculum require the teacher to be only one source of learning, because the teacher acts as a facilitator. This service will help overcome the problem of low professional and pedagogic competence of junior high school teachers, especially in designing and using worksheets as learning resources in learning. The method used is training with discussion techniques, question and answer, simulations, and assignments. The training subjects were 25 junior high school teachers in Bandar Lampung City. The instruments used were observation, tests and structured interviews. The success of the service was analyzed descriptively by percentage. After the training, there was a good increase in 1) the training process went well and enthusiastically, (2) there was an increase in the knowledge and skills aspects of breastfeeding LKPD. The results of the pre-test conducted before the training for all indicators of knowledge and skills were in the pretty good category. The results of the post test, there is only 1 indicator in the good category, namely the LKPD concept, and other indicators are in the very good category. For the skill aspect, there is 1 indicator in the good category, namely drawing arrangement, and the other indicators are in the very good category.